Use of statistical parametric mapping to reveal novel athletespecific kinetic determinants of sprint start performance - Colyer, S. L.; Salo, A. I. T. (ISBS Proceedings Archive (Michigan), 2017)
The powerful development of force largely determines sprint start performance. However, to date, block phase kinetics have only been examined using discrete (0D) variables. One male sprinter completed 16 sprint starts whilst the ground reaction forces applied by each limb were measured. Kinetic predictors of horizontal external power were identified using Pearson r for 0D variables and statistical parametric mapping (SPM) to assess entire force curves. Pearson`s correlations revealed fast horizontal force production to result in better performance, but maximum forces appeared important only for the rear leg. Conversely, SPM results suggested that horizontal forces in the early push phase (initial 15-30%) were important for both legs. Testing entire force curves using SPM can supplement 0D analysis to identify kinetic factors which would otherwise be undetected.